Metal-free access to hindered N-alkyl sulfoximines via in-situ generated Aza-oxyallyl cations from functionalized alkyl bromide - More, Satish G.; Mane, Kishor D.; Suryavanshi, Gurunath (Asian Journal of Organic Chemistry, 2022)
Herein, we report a catalyst-free and mild synthetic method for the construction of hindered N-alkyl sulfoximines derivative. A wide range of hindered di-alkyl sulfoximines can be readily obtained from the reaction of alpha-bromo-hydroxamates with a variety of sulfoximines, including diaryl, aryl-alkyl, di-alkyl and heteroaryl sulfoximines.
Keywords: alpha-Bromo hydroxamates; Aza-oxyallyl cations; Di-alkyl sulfoximines; metal-free; Sulfoximines